Benign infantile seizures followed by autistic regression in a boy with 16p11.2 deletion. Issue 2 (June 2017) - Milone, Roberta; Valetto, Angelo; Bertini, Veronica; Sicca, Federico
Abstract: Benign infantile seizures (BIS) are usually a self‐limiting condition, which may be associated with heterozygous mutations in the PRRT2 gene at chromosome 16p11.2. Here, we report a boy with a deletion in 16p11.2, presenting with BIS and typical neurodevelopment in the first year of life, unexpectedly followed by severe autistic regression. 16p11.2 deletions are typically associated with intellectual disability, autism, and language disorders, and only rarely with BIS. This clinical report shows that the neurodevelopmental prognosis in BIS patients may not always be benign, and suggests that array CGH screening should be considered for affected infants in order to rule out deletions at 16p11.2 and long‐term clinical follow‐up.